Thematic-based Literature Learning Assistance to Improve Numeracy Literacy Skills at Elementary School Level - Ritonga, Mara Untung; Wuryani, Elly Prihasti; Nasution, Rizki Fadila (Universitas Negeri Medan, 2024)
In today's technological era, the flow of information flowing into society is so swift. For this reason, students are required to master a variety of information and knowledge materials. Reading skills play a very important role in everyday life. But not just reading the words, reading skills include the ability to understand the explicit and implied meaning of sentences, paragraphs, and the whole text as a unit. This shows that reading is a complex and challenging process. Reading skills are also formed through a series of long processes. Therefore, learners starting from the primary school level need to master strategies to improve reading skills in all subjects to understand learning materials. Learners should be taught reading skills according to their level. Without mastering reading skills at their level, learners will not be able to access knowledge. Reading skills are also a measure of global competence tested in the Program for International Student Assessment (PISA). Unfortunately, the reading scores of Indonesian students continue to decline from year to year. Seeing these conditions, strengthening literacy in Indonesian language subjects needs to be done by teachers as the frontline of the nation's education process. Teachers are expected to assist students to understand reading material and train students to reason through reading texts.